The Influence of Trust, Privacy, and Quality of Service on the Success of E-CRM through Customer Satisfaction in the Use of ShopeePay - Siti Nurjannah; Nonik Kusuma Ningrum; Putri Dwi Cahyani (Dinasti International Journal of Education Management And Social Science, 2024)
This study examines the impact of Trust, Privacy, and Quality of Service on the success of the E-CRM system in fostering relationships with ShopeePay users, focusing on ShopeePay in Indonesia. ShopeePay are widely used in daily activities, and this research highlights customer satisfaction in their use. The study identifies three key variables Trust, Privacy, and Quality of Service that influence E-CRM success. Using a quantitative approach, 190 respondents were surveyed, and data was analyzed with IBM SPSS Statistics 25. Results show that Privacy and Quality of Service significantly affect customer satisfaction and the effectiveness of the E-CRM system in building relationships with ShopeePay users..